Pengembangan Lembar Kerja Peserta Didik Elektronik Berbasis Keterampilan Proses Sains Materi Sel Kelas XI SMA - Agustini, Ariani; Adnan, Adnan; Arifin, Arifah Novia (Universitas Negeri Makassar, 2022)
Abstract. Electronic Student Worksheets (LKPD) based on Science Process Skills (KPS) on Cell material with the aim of producing electronic LKPDs that can help solve problems in the field and meet valid and practical criteria. Material development and design of electronic worksheets using the Moodle LMS. This type of research is Research and Development (R&D) with the ADDIE development model which has five stages, namely analysis, design, development, implementation, and evaluation. The subjects of this study were expert lecturers who carried out the validity of the instruments and products developed, Biology subject teachers, and students of class XI MIA 3 SMA Negeri 1 Soppeng as subjects to test the practicality of the product. The results showed, that the developed electronic LKPD product is valid and practical. Thus, it can be concluded that the KPS-based electronic LKPD in the class XI high school cell material developed is suitable for use in the learning process.Keywords: electronic student worksheets, ADDIE, science process skills, cells.